Innovation from emerging markets : from copycats to leaders - Cahen, Fernanda Ribeiro; Miroux, Anne; Casanova, Lourdes (Cambridge : Cambridge University Press, 2021)
In recent years, emerging markets have come to represent the largest share of global GDP and have made gains in economic development and political influence. In turn, emerging market companies have taken on a new level of importance in driving innovation, local development and global competition. Advancing an integrative view that captures the diversity of innovation among companies in emerging markets, this book highlights the rapid evolution of emerging markets from imitators to innovation leaders. Building upon research conducted by the Emerging Multinational Research Network (EMRN) in collaboration with several universities in North and South America, Europe and China, this rich and expansive collection includes studies of innovation in regions yet to receive focused analysis in the field. The authors also re-examine dominant theories of innovation and capability creation based on a broad range of case studies and research insights. Offering a taxonomy of emerging market innovations, this collection reveals the unique drivers, types, and outcomes of innovation in emerging markets.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Technological innovations -- Economic aspects -- Developing countries; New business enterprises -- Developing countries; New products -- Developing countries